Protective effects of seed melon extract on CCl4-induced hepatic fibrosis in mice. (4th December 2016) - Zhan, Yuan-Yuan; Wang, Jin-Hui; Tian, Xing; Feng, Shi-Xiu; Xue, Lin; Tian, Li-Ping
Abstract: Ethnopharmacological relevance: Citrullus lanatus ssp. vulgaris var. megalaspermus Lin et Chao, was also known as watermelon belongs to family Cucurbitaceae, variously used as healthy food and in the treatment of liver and lungs problems. Currently, Citrullus lanatus has become a major economic crop of medicinal and edible effects with regional characteristics. Aim: This study was designed to evaluate the hepatoprotective and antioxidant activity of the seed melon ( Citrullus lanatus ssp. vulgaris var. megalaspermus Lin et Chao) extract (SME) against carbon tetrachloride (CCl4 ) induced hepatic fibrosis in mice. Materials and methods: In this study, mice were randomly divided into 7 groups, including normal control, model, silymarin tablets as the positive control, SME 100, 200, 400, and 800 mg/kg. After 8 weeks, activities of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), triglycerides (TG), hyaluronic acid (HA) and laminin (LN) were checked. The levels of antioxidant enzymes such as superoxide dismutase (SOD), glutataion (GSH) and glutathione peroxidase (GSH-Px) were determined after SME administration. The hydroxyproline (HYP) levels, malondialdehyde (MDA) levels and histopathologic examinations of hepatocyte fibrosis were also determined. Additionally, effects of SME on alpha-smooth muscle actin ( α -SMA) and transforming growth factor beta-1(TGF- β 1) protein expressions were determined. Results: We found that SME could significantly lower the serum levels of hepatic enzyme markers AST, ALT, HA and LN ( P< 0.01). Compared with the CCl4 -only treatment group, levels of hepatic SOD and GSH-Px were significantly increased, and the MDA levels were remarkably decreased in mice treated by SME at medium dose (400 mg/kg) and high dose (800 mg/kg) ( P< 0.01). A histological examination of the liver showed that lesions, including necrosis, lymphocyte infiltration and fatty degeneration, were partially healed by treatment with SME. The results of protein expressions studies displayed that SME could inhibit α -SMA and TGF- β 1 protein expression (P< 0.01). Conclusion: The present results suggested that protective effect of SME against CCl4 -induced hepatic fibrosis may rely on its effect on reducing oxidative stress and improving drug metabolizing enzyme activity in liver. Graphical abstract: